The commercialisation of computing artefacts and technological entrepreneurship in university incubation program - Tamrin Amboala; Syed Nasirin Syed Zainol Abidin; Suddin Lada; Esmadi Abu Abu Sema; Iza Azura Ahmad Bahar (Institute of Electrical and Electronics Engineers, 2021)
There is a general agreement in terms of the execution processes to support inventions of prototypes and products which begins from prototyping to the actual market. However, the mechanism and process to translate the academics research from university to the industry are questionable since the success of commercialisation of computing research artefacts is disputed. This article attempts to investigate the commercialization mechanism and processes for these artefacts from universities. The investigation is carried out in selected university incubations as a case study research. Resource-based and capability perspective are adapted to investigate the selected cases in the university technology commercialization initiatives. The outcomes of this article are expected to offer a commercialisation model of computing artefacts among academics.